South Asia - Mukherji, Aditi; Kishore, Avinash; Rashid, Shahidur (2022)
Aditi Mukherji, Avinash Kishore, Shahidur Rashid GLOBAL FOOD POLICY REPORT 2022 Global Food Policy Report: Climate Change & Food Systems Global Launch Event MAY 12, 2022 - 9:30 TO 11:00AM EDT